Modern language postgraduate studies at ECCI University (2014)
This project seeks to provide the possible lines of post graduate studies, which graduates of modern languages' Major can take in order to improve their professional profile and labor profile. In order to reach truthful results and supported by probable theories is presented the comparison between the study plan of Modern Languages' Major in La Escuela Colombiana de Carreras Industriales against nine universities in Latin America which offer similar studies.